SCHOOL’S SITUATIONAL LEADERSHIP PRACTICES IN THE MIDDLE OF HEALTH CRISIS - O. Siat, Gregg (International Journal of Rehabilitation and Special Education (IJRSE), 2024)
This study aimed to determine the school’s situational leadership practices amongthe Calubian North District leaders in the middle of a health crisis. The descriptive-correlational method was employed, with the survey questionnaire as the main datagathering tool, with school leaders, teachers, parents, and the Local Government Unit asrespondents of the study. The majority of the teachers belong to the age range of 51-60years old; with regard to their sex, 12 out of 15 school leaders are female; as for civilstatus, 2 of them are single, and 13 are married; most of them have a BS with MA units;7 of them hold a position as Teacher In-Charge, 5 are Head Teacher I, 1 is Principal I,and 1 is Principal II; and the majority of them attended training at the district level, withonly 3 attending at the international level. The situational leadership practices employedby the elementary teachers in the new normal in terms of access were rated with anaverage mean of 4.34, interpreted as often; regarding quality, the average mean was4.15, inferred as often; and for governance, it has an average mean of 4.03, interpretedas often. As for the stakeholders’ level of support from the teachers, the average meanwas 4.16, described as “always”; support from the Local Government Unit receivedan average mean of 4.08, described as “high,” and the support of parents obtained anaverage mean of 4.22, interpreted as “high.” There was a significant relationship betweenthe profile of the school leaders and their situational leadership practices, and there wasa significant relationship between the school leaders’ situational leadership practicesand stakeholders’ level of